Gender Equality in Article 1 of the Universal Declaration of Human Rights: An Islamic Law Perspective - Jalaludin, Diding; Arifin, Tajul; Fauzia, Ine (MAQASIDI: Jurnal Syariah dan Hukum published by the Islamic Criminal Law Program of the Sharia and Islamic Economics Department at the Sekolah Tinggi Agama Islam Negeri Teungku Dirundeng Meulaboh, 2024)
This study aims to determine the relevance of Article 1 of The Universal Declaration of Human Rights which guarantees freedom, dignity and equal rights between human individuals from the perspective of Islamic Law which came with the vision of rahmatan lil 'alamin through the Prophet Muhammad Shallahu 'Alaihi Wasallam. The method used in this research uses a descriptive analysis method with a normative juridical approach and uses qualitative data types in the form of secondary data consisting of primary, secondary, and tertiary legal materials with data collection techniques through literature studies and content analysis techniques. This research concludes that there is a significant relevance where Islamic Law greatly strengthens and provides hujjah to the clause of gender equality position between individuals that has been formulated in Article 1 of The Universal Declaration of Human Rights. So the existence of several differences in concepts between men and women in the perspective of Islamic Law is not a discrimination against certain genders, the existence of these differences has placed each gender in a noble position based on its characteristics as conceptualized by Islamic law.